2017
DOI: 10.31248/jbbd2016.018
|View full text |Cite
|
Sign up to set email alerts
|

Survivability, growth performance and nutrient composition of the African Palm Weevil (Rhyncophorus phoenicis Fabricius) reared on Four different substrates

Abstract: Survivability, growth performance and nutrient composition of the African Palm weevil (APW) (Rhyncophorus phoenicis) reared on four different substrates was investigated following earlier finding that Sugar cane tops (SCT) and Spoilt water melon (SWM) could be useful in captive rearing of the weevil. This necessitated a search into other waste fruits that could be used as media for rearing of APW as their infestation of oil and raffia palm is not only unfriendly to the environment but also wastage of economic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…When vermiwash (water washings of earthworm cocoons) at 10%, 25% or 50% was sprayed on mulberry leaves and fed to fifth instar B. mori larvae, significant increases on a dose-dependent basis were observed with regard to carbohydrates, protein and fat [ 93 ]. However, when Ebenebe et al [ 94 ] reared R. phoenicis larvae on four organic substrates, e.g., sugarcane tops, split watermelon, split pineapple and raw papaya, their larvae had (on dry weight basis) normal carbohydrate, protein and fibre, contents that did not vary much and statistical significance was lacking. They concluded that split pineapple can be selected for feeding larvae as a potential source of protein and fluid.…”
Section: Nutrient Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…When vermiwash (water washings of earthworm cocoons) at 10%, 25% or 50% was sprayed on mulberry leaves and fed to fifth instar B. mori larvae, significant increases on a dose-dependent basis were observed with regard to carbohydrates, protein and fat [ 93 ]. However, when Ebenebe et al [ 94 ] reared R. phoenicis larvae on four organic substrates, e.g., sugarcane tops, split watermelon, split pineapple and raw papaya, their larvae had (on dry weight basis) normal carbohydrate, protein and fibre, contents that did not vary much and statistical significance was lacking. They concluded that split pineapple can be selected for feeding larvae as a potential source of protein and fluid.…”
Section: Nutrient Contentsmentioning
confidence: 99%
“…The highest protein (32.0%) and fibre (8.4%) content was found in R. phoenicis larvae fed on oil palm yolk. Practically, year-round non-availabilities of some plant materials and the costs involved to procure them make vegetative substrates often uneconomic for mass production by farmers and tribal communities [ 94 ].…”
Section: Nutrient Contentsmentioning
confidence: 99%
“…They begin to hatch after three days, whereby the larvae tunnel into the crown and trunk. Moreover, the larvae are legless (apodous), yellowish-white in colour and have brown heads (Ebenebe et al, 2017). APW larvae may reach 5-6 cm in length and have brown edges displaying bristles (Mba et al, 2018).…”
Section: General Morphology Of Rhynchophorus Phoenicismentioning
confidence: 99%
“…Insects are often considered a nuisance to humans and mere pests for both crops and animals. Nonetheless, they are also a food source with a low environmental impact and cost, and tend to contribute positively to small-scale livelihoods, in addition to playing an important role in nature (Muafor et al, 2012;Ebenebe et al, 2017). However, the public remains largely unaware of these benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary findings in artificial production of palm weevil larvae are promising [19]. Massive palm grub production is in pilot stages with some important success [19][20][21][22][23]. Substrates and microclimate conditions have been mastered and trials already done under farmers' conditions [22].…”
Section: From Harvesting To Farmingmentioning
confidence: 99%